SEROPREVALENCE OF ANTIBODIES AGAINST Toxoplasma gondii IN ALPACAS OF A BREEDING CENTRE IN CUSCO, PERU - Angulo T., José (2014)
The aim of this study was to determine the seroprevalence of anti-Toxoplasma gondiiantibodies in alpacas of a breeding centre in the province of Canchis, Cusco, Peru, by theindirect inmunofluorescence technique (IFAT) using a cut off of 1:200. A total of318blood samples were collected from female alpacas. The seroprevalence was of 25.8 ± 4.8% (82/318). Out of 82 positive sera, 62.2% showed titres of 1:200. The results confirmthe presence of specific anti-T. gondii antibodies in alpacas in Cusco